Aerosol and cloud properties over a coastal area from aircraft observations in Zhejiang, China. (15th December 2021) - Che, Yunfei; Zhang, Jing; Fang, Chungang; Zhou, Xu; Xue, Wenhao; Hu, Xiaomin; Duan, Jing; Li, Wei; Gao, Yang; Lu, Guangxian; Zhao, Delong; Zhao, Chuanfeng
Abstract: Using in-situ aircraft observations from six flights over Zhejiang on Sep. 1 and Sep. 4, 2016, this study investigates differences in aerosol and cloud properties between daytime and nighttime. The samples were divided into marine type and continental type based on the backward air mass trajectories and aerosol characteristics. The results show that the aerosol number concentration (Na ) near the ground during daytime is higher than that at nighttime. During daytime, Na has a significant decreasing trend near the top of the planetary boundary layer (PBL), which is not obvious during nighttime. There may be still a relative high concentration of aerosols remaining in the transition zone between the PBL and the free troposphere. Under similar liquid water content (LWC) conditions, the cloud droplet number concentration (Nc ) at night is lower, and the cloud droplet effective diameter (cloud ED) is larger. The total Na of marine type aerosols is generally lower than that of continental type aerosols, but for aerosols with particle diameters greater than 1 μm, the marine type aerosols are higher. The study shows a strong negative Na -cloud ED relationship for marine type aerosols, but no obvious Na -cloud ED relationship for continental type aerosols. The number of cloud condensation nuclei (CCN) is higher under high-Na conditions; the ratio of CCN to Na reveals that the activation efficiency of marine type aerosols is higher than that of continental type aerosols. There is no obvious difference in activation efficiency between day and night. Highlights: Aerosol and cloud properties between daytime and nighttime were investigated. Na decreases around BLH during daytime, but the trend is not obvious at nighttime. Marine type aerosols show a strong negative Na -cloud ED relationship.